ANALISA KADAR VITAMIN C PADA FORMULASI CINCAU BERBAHAN DASAR DAUN BINAHONG (ANDREDERA CORDIFOLIA) - Agustina Dyah Setyowati; Ade Irawan; Sulanjari Sulanjari; Noviana Imamila Mar’ati; Rina Rahmawati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Anredera Cordifolia is a plant that has recently attracted the attention of herbalists and the public as a herbal remedy. Binahong (Anredera Cordifolia) is commonly used for its leaves, tubers, and flowers as medicine. Binahong leaves (Anredera Cordifolia) contain active compounds such as alkaloids, flavonoids, terpenoids, and saponins. Binahong leaves are also a herb that contains vitamin C. Vitamin C is a substance needed by the body that acts as an antioxidant. Vitamin C has two active molecules: a reduced molecule (Ascorbic Acid) and an oxidized molecule (Dehydro Ascorbic Acid). Vitamin C functions in collagen formation in tissues, tooth bonding, tyrosine metabolism, and neurotransmitter synthesis. Furthermore, vitamin C plays a major role in the formation of intercellular collagen. Collagen is a protein compound found primarily in cartilage, the inner layer of bones, dentin, and vascular endothelium. The purpose of this study is to make new innovations on processed binahong leaves (Anredera Cordifolia) in the form of binahong leaf grass jelly, analyze and determine the levels of vitamin C contained in binahong leaves (Anredera Cordifolia) and observe the public's acceptance of binahong leaf grass jelly. The research method used is experimental analytic with quantitative and qualitative analysis using the Uv-Vis spectrophotometry method and acceptance. This study used two experiments with the addition of 140 grams and 180 grams of binahong leaves and the results of the analysis of levels From the quantitative test on the uv-vis spectrophotometry method, the vitamin C content in binahong leaves (Anredera Cordifolia) did not experience a significant decrease and the optimum condition point of the vitamin C content in the test treatment at 120 hours in a sample of 180 grams of binahong leaves (Anredera Cordifolia) with a vitamin C content of 0.393942519. and For the acceptance test using a hedonic test for color, aroma and preferred taste and texture. It can be concluded that binahong leaves have high levels of vitamin C. From the results of the hedonic test, it can be concluded that there are differences in the two samples in terms of aroma and taste, while in terms of color there are insignificant differences, while in terms of texture there is no difference between the two samples.Keywords: Binahong Leaves, Acceptability, UV-Vis Spectrophotometry, Vitamin C